The Role of Genre-Based Activities in the Writing of Argumentative Essays in EFL - Chala Bejarano Pedro Antonio; Chapetón Claudia Marcela (Universidad Nacional de Colombia, 2013)
<span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">This article presents the findings of an action research project conducted with a group of pre-service teachers of a program in modern languages at a Colombian university. The study intended to go beyond an emphasis on linguistic and textual features in English as a foreign language argumentative essays by using a set of genre-based activities and the understanding of writing as a situated social practice. Data were gathered through questionnaires, semi-structured interviews, class recordings, and students' artifacts. The results showed that genre-based activities supported the participants throughout the experience and boosted their confidence, resulting in a positive attitude towards essay writing. The study highlights the importance of dialogic interaction to provide scaffolding opportunities, of understanding writing as a process, and of the use of samples and explicit instruction to facilitate writing. <span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">Este artículo presenta los hallazgos de una investigación-acción realizada con un grupo de estudiantes de la licenciatura en Lenguas Modernas de una universidad colombiana. El estudio buscaba ir más allá del énfasis en las características lingüísticas y textuales en la escritura de ensayos argumentativos en inglés como lengua extranjera, mediante un conjunto de actividades basadas en géneros y comprendiendo la escritura como una práctica social situada. Los datos se obtuvieron a través de cuestionarios, entrevistas semiestructuradas, grabaciones de clase y artefactos de los estudiantes. Los resultados muestran que las actividades basadas en la enseñanza de géneros proporcionan apoyo a los participantes durante la experiencia investigativa y aumentan su confianza y actitud positiva hacia la escritura de ensayos. El estudio resalta la importancia de la interacción dialógica para ofrecer oportunidades de andamiaje, la escritura como proceso y el uso de muestras e instrucción explícita para facilitar la escritura.